Evaluating the combustion process of methane fired cross draft ceramic kiln for efficiency and sustainability - Ezra Abubakar; Sunday Mbidomti; Mary Lawan; Nasruddeen Abubakar (Sustinere: Journal of Environment and Sustainability, 2023)
Sustainable ceramic production is not only dependent on the adoption of renewable fuel, but also on combustion proficiency, efficient fuel utilization, and thermal energy released. This study reports on the thermal evaluation of a cross-draft ceramic kiln, with a view to determine the efficiency of the combustion process. The methodology involved firing the kiln to determine the equivalent ratio, stoichiometric air-methane ratio, enthalpy of formation of reactants and products, and the thermal energy liberated from the firing process. The results indicated that: 1000°C is attainable in 7 hours and 30 min at a firing rate of 136.97 sec/°C, fuel consumption rate of 1L/61.6 sec and average temperature of 613.4°C. The results also showed that, enthalpies of formation of products and reactants of -74,897 and -557,376.843 were generated at air-methane equivalent ratio of 1 : 5 and stoichiometric ratio of 9.818. This translated to 57.18% of air available for the combustion process and a 42.82% deficiency. The study concluded that though the combustion process of the methane fired kiln was weak, resulting in thermal energy loss of 39.9%, there was an energy utilization of up to 60.1%.